2018
DOI: 10.1371/journal.ppat.1007307
|View full text |Cite
|
Sign up to set email alerts
|

A polymorphic residue that attenuates the antiviral potential of interferon lambda 4 in hominid lineages

Abstract: As antimicrobial signalling molecules, type III or lambda interferons (IFNλs) are critical for defence against infection by diverse pathogens, including bacteria, fungi and viruses. Counter-intuitively, expression of one member of the family, IFNλ4, is associated with decreased clearance of hepatitis C virus (HCV) in the human population; by contrast, a natural frameshift mutation that abrogates IFNλ4 production improves HCV clearance. To further understand how genetic variation between and within species affe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
68
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(81 citation statements)
references
References 72 publications
13
68
0
Order By: Relevance
“…Using these data, we observed that the haplotype coding for the IFN-λ4-S70 variant had a smaller effect on viral amino acid variability compared to the haplotype coding for the IFN-λ4-P70 variant. This observation agrees with previous independent studies showing the reduced antiviral activity for IFN-λ4-S70 in vitro (Bamford et al, 2018; Terczyńska-Dyla et al, 2014). Moreover, the mean viral load in IFN-λ4-Null carrying patients was similar to those carrying the IFN-λ4-S70 variant; by contrast, those carrying an IFN-λ4-P70 variant had a reduced viral load, which correlates with its higher antiviral activity.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Using these data, we observed that the haplotype coding for the IFN-λ4-S70 variant had a smaller effect on viral amino acid variability compared to the haplotype coding for the IFN-λ4-P70 variant. This observation agrees with previous independent studies showing the reduced antiviral activity for IFN-λ4-S70 in vitro (Bamford et al, 2018; Terczyńska-Dyla et al, 2014). Moreover, the mean viral load in IFN-λ4-Null carrying patients was similar to those carrying the IFN-λ4-S70 variant; by contrast, those carrying an IFN-λ4-P70 variant had a reduced viral load, which correlates with its higher antiviral activity.…”
Section: Discussionsupporting
confidence: 93%
“…This variant [ΔG > TT] causes a frameshift, abrogating production of functional IFN-λ4 protein (Prokunina-Olsson et al, 2013). Moreover, several amino acid substitutions within IFN-λ4 have been shown to alter its antiviral activity (Bamford et al, 2018; Terczyńska-Dyla et al, 2014). In particular, a common amino acid substitution (coded by the SNP rs117648444 [G > A]) in the IFN-λ4 protein, which changes a proline residue at position 70 (P70) to a serine residue (S70), reduces its antiviral activity in vitro (Terczyńska-Dyla et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…These results were similar to our previous analyses (11). SGRs containing mutations had reduced replication in EGFP-CM-treated cells compared to WT (Fig 2C), consistent with data presented in Fig 2A at 48hpt (Fig 2A).…”
Section: The Region Encompassing A150v and An Additional Cluster Of Isupporting
confidence: 92%
“…One of our main objectives in the study was to examine whether A150V, which is associated with host IFNL4 genotype, would affect multicycle HCV replication in the presence or absence of IFNλ4 using an in vitro model system. We have previously established a system to test the antiviral activity of WT human IFNλ3 and IFNλ4 on HCV infection (11). Huh7 cells, treated with exogenous transfected-cell 'conditioned media' (CM) containing IFNs, were transfected with WT and mutant SGR RNAs or infected with WT and mutant HCVcc; GLuc activity was assayed at 48hpt (for SGR) and viral RNA measured at 72hpi (for HCVcc).…”
Section: The Region Encompassing A150v and An Additional Cluster Of Imentioning
confidence: 99%
“…One of the limitations of using human IFN-λ as a universal therapeutic molecule resides in the fact that it has several genetic variants (20,21) that might have different stability and affinity in the interaction with the IFNLR. Engineering of IFN-λ to assess natural or in silico predicted mutations critical to maintaining the antiviral activity proved that the strength of the interaction of between IFN-λ and its receptor could modulate downstream functions (22)(23)(24)(25)(26).…”
Section: Introductionmentioning
confidence: 99%